Ecological-based insights into bat populations in the Yucatán Peninsula under a One Health approach: coexistence or biophobia - Sánchez-Soto, Ma. Fernanda; Gaona, Osiris; Mercado-Juárez, Ricardo; Yanez-Montalvo, Alfredo; de León-Lorenzana, Arit; Borja-Martínez, Gabriela; Zaldívar, Daniela; Rodríguez-González, Stephany; Hernández-Villegas, Erika N.; Moreira-Soto, Andres; Drexler, Jan Felix; Suzán, Gerardo; et al. (Frontiers in Conservation Science, 2025)
The Yucatán Peninsula (YP) is home to approximately 60 bat species with differing feeding strategists that, collectively, are fundamental for the health of tropical forests. During the SARS-CoV-2 pandemic, biophobic (aversive) responses towards bats were recorded in urban and rural areas of the YP, making evident the need to monitor bat diversity, investigate species’ biology (e.g., microbiome) and, perhaps most importantly, conduct educational activities that foster an affinity for bats. We designed a multi-scale effort to characterize bat populations and their gut microbiome in urban (Mérida), agricultural (Tizimín), and conserved (Calakmul) landscapes of the YP, while conducting outreach activities to promote biophilic responses. In general, children showed positive responses toward bats, recognizing that they are important parts of their environment. A total of 308 bats from 18 species were sampled; frugivorous species were the most abundant guild (93%), represented mainly by Artibeus jamaicensis and Artibeus lituratus, followed by insectivorous species. Conserved and agricultural landscapes harbored 11 and 16 bat species respectively, both with higher diversity than the suburban areas (eight species). Findings suggest that land use differences in the YP are a factor affecting bat diversity, as well as bat microbiome diversity. Gut microbiome was mainly composed of Pseudomonadota, Bacillota and Actinobacterota (>90%), and abundant bacterial families included Enterobacteriaceae, Staphylococcaceae and Streptococcaceae. Our results have set the baseline for zoonotic disease screening and prevention in the YP, highlighting the importance of coexistence with bats given their key role in maintaining the health of ecosystems.